2013
DOI: 10.1093/brain/awt159
|View full text |Cite
|
Sign up to set email alerts
|

Network oscillations modulate interictal epileptiform spike rate during human memory

Abstract: Eleven patients being evaluated with intracranial electroencephalography for medically resistant temporal lobe epilepsy participated in a visual recognition memory task. Interictal epileptiform spikes were manually marked and their rate of occurrence compared between baseline and three 2 s periods spanning a 6 s viewing period. During successful, but not unsuccessful, encoding of the images there was a significant reduction in interictal epileptiform spike rate in the amygdala, hippocampus, and temporal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 42 publications
8
80
0
Order By: Relevance
“…Network oscillations, like the spike-preceding gamma, may help elucidate the neuronal processes underlying epileptiform activities, as demonstrated in a recent study using a rat model of epilepsy. 5 The relationship between network activity and IEDs has recently been applied to study the effect of cognitively induced oscillations on IED suppression, 9 opening a possibility for treating interictal pathophysiology. Further research will show whether the gamma-IEDs, physiological HFOs associated with normal function, 10 and seizures share common network processes and thus drive new treatments and therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Network oscillations, like the spike-preceding gamma, may help elucidate the neuronal processes underlying epileptiform activities, as demonstrated in a recent study using a rat model of epilepsy. 5 The relationship between network activity and IEDs has recently been applied to study the effect of cognitively induced oscillations on IED suppression, 9 opening a possibility for treating interictal pathophysiology. Further research will show whether the gamma-IEDs, physiological HFOs associated with normal function, 10 and seizures share common network processes and thus drive new treatments and therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were aware that they might be asked to recall the images 24 h later. Details of the protocol have been described previously (Matsumoto et al 2013).…”
Section: Tasksmentioning
confidence: 99%
“…In humans, direct intra-MTL depth recordings and/or cortical surface recordings have shown that presentation of a subsequently remembered stimulus resets theta activity or alters theta power in the hippocampus, rhinal cortex, and/or amygdala [10,12-14,19,20], as well as temporal, frontal, and/or parietal-occipital association cortices [21-24]. Shifts in other frequency bands tend to co-occur with these shifts in theta.…”
Section: Low-frequency Responses and Memorymentioning
confidence: 99%
“…Shifts in other frequency bands tend to co-occur with these shifts in theta. Specifically, theta and alpha phase resets in temporal, parietal, and occipital cortices [21]; theta, alpha, and beta phase resets [12] or power decreases [20] in the MTL; and right cortical theta power increases in the midst of widespread gamma increases [25] have been linked to SM. Employing SUA measurements, Rutishauser et al [19] reported that theta phase resets are tightly coupled with local spiking activity – i.e., theta phase-SUA coupling (see [26]).…”
Section: Low-frequency Responses and Memorymentioning
confidence: 99%
See 1 more Smart Citation